Influence of the constraints associated with the numerical game situations on the technical-tactical actions of U-11 football players in Spain - García-Angulo, F. J.; García-Angulo, A.; Giménez-Egido, J. M.; Ortega-Toro, E. (International Journal of Sports Science & Coaching, 2024)
The aim of the present study was to analyse the influence of the constraints led approach (CLA) systems, such as the playing space, the number of players and the numerical game situations (superiority, equality and numerical inferiority) on the technical-tactical actions of U-11 players in small-sided games (SSGs). A case study was developed where two of the CLA constraint systems were applied on three SSG where the dimensions of the game space were modified (SSG1: 160 m2 ; SSG2 and SSG3: 155 m2 ) and the numerical game situation against the opposing team (SSG1: equality; SSG2 and SSG3: superiority/inferiority). The study sample consisted of U-11 players (n = 8) competing at federated level in Spain (10.25 ± 0.45 years; 2.21 ± 0.61 years of experience). The results of this study show an very strong degree of association between the game modalities and the way of obtaining the ball (2Ln(BFp10) = 10.06) and a strong association between the game modalities and the zone of origin of the ball (2 Ln(BFp10) = 6.02). It should be noted that a positive association was found between games modes and ball height in obtaining the ball (2Ln(BFp10) = 4.06); type of conduction (2Ln(BFp10) = 5.88); technical action (2Ln(BFp10)= 2.32) and efficiency (2Ln(BFp10) = 4.04). These data can help coaches to optimize the training process of young players by modifying the training tasks based on the constraint systems proposed in this study.